Shark sandwich. - Siukola, Jussi; Dahlblom, Tuomo, 1978-; Joensuu, Jaro; Leppänen, Tapio; Lievemaa, Tommi, 1966- ([kustannuspaikka tuntematon] : Siukolan Jytä, 1999)
11 kappaletta.
Sanat tekstiliitteessä.
Jussi Siukola (lauluääni, kitara), Tuomas Dahlblom (kitarat), Jaro Joensuu (rummut), Tapio Leppänen (basso), Tommi Lievemaa (kitara, taustalaulu), vierailijat: Juha Johansson (huilu), Anssi Kettunen (saksofoni), Petteri Pitkänen (harmonikka, urut), Anita Seppä (kitara/Rattlesnake), Niina Koskinen (basso/Rattlesnake), Timo Lievemaa (rummut/Rattlesnake).
Äänitys: 1995, 1997, 1998, Jyväskylä, Studio Kaktus.
Keywords: Siukola, Jussi -- albumit; rock and roll; surfmusiikki